The effects of strength vs. plyometric training on sprinting kinetics in post peak height velocity (PHV) female athletes - Talukdar, K.; Harrison, C.; McGuigan, M. R. (Sports Biomechanics, 2021)
Speed is a crucial factor for overall athletic development. While researchers have shown strength and plyometric training to improve sprinting speed in some adult and youth populations, no studies have compared the effects of strength and plyometric training on sprinting speed in young females. Fifty-two young females were divided into three groups and trained for 7 weeks, twice a week; strength training (n = 16, age 13.36 ± 0.84), plyometric training (n = 21, age 13.38 ± 0.75) and a physical education class as a control group (n = 15, age 13.95 ± 0.54). Participants were tested for sprinting performance and horizontal force (Fo), maximum velocity (Vmax) and maximum horizontal power (Pmax) metrics over 30 m distance, isometric strength and unilateral horizontal jump distance before and after the intervention. Both the strength and plyometric groups significantly improved all performance variables (p < 0.05). The strength group significantly improved 10 m split time (6.76%; Hedge's g = 0.65) and Fo (18.98%; g = 0.67), whereas the plyometric group significantly improved Vmax (4.91%; g = 0.50) and Pmax (7.91%; g = 0.31). The findings of this study suggest that both strength and plyometric training can improve sprinting kinetics, jumping performance and overall strength in young females.